The Challenge of Boko Haram in Nigeria and Lessons from the Sierra Leone Civil War - Portaankorva, Jari (Journal of European Baptist Studies, 2024)
The civil war in Sierra Leone was one of the most vicious conflicts in Africa’s recent history. Baptists and other religious communities worked together to end the conflict between the government and the Revolutionary United Front (RUF). Today, Nigeria has similar challenges and there is a need for close cooperation between religious communities to mediate peace between the government and Boko Haram. Faith-based peacebuilding aims at a just peace and reconciliation through non-violent means, and this study compares faith-based peace building in Sierra Leone during the 1990s with the Boko Haram uprising in Nigeria today and considers the lessons to be learnt. The article discusses how the efforts of faith-based peace building actors in Nigeria may support both the peace process and the peaceful coexistence of religious communities, arguing that within this there is an urgent need to discuss poverty and social marginalisation, build stronger relationships between governments and local communities, and open direct dialogue with Boko Haram.